2023
DOI: 10.3390/math11030555
|View full text |Cite
|
Sign up to set email alerts
|

A New Incommensurate Fractional-Order COVID 19: Modelling and Dynamical Analysis

Abstract: Nowadays, a lot of research papers are concentrating on the diffusion dynamics of infectious diseases, especially the most recent one: COVID-19. The primary goal of this work is to explore the stability analysis of a new version of the SEIR model formulated with incommensurate fractional-order derivatives. In particular, several existence and uniqueness results of the solution of the proposed model are derived by means of the Picard–Lindelöf method. Several stability analysis results related to the disease-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Several fractional studies of deterministic, stochastic and incommensurate models on COVID-19 illness were delved in the literature examining various fear factors, diagnosed, threatened, awareness of pathogen spread, vaccination schemes, vaccine hesitancy, vaccine inefficacy, treatment, isolation, exposure to the virulent environment, effective vaccination with self-precautions, vaccine breakthrough infections, symptomatic and asymptomatic carriers and mutant strains, and so on. [30][31][32][33][34][35][36][37][38][39][40][41][42] COVID-19-related coinfections were studied with other superinfections namely hepatitis-B, 43 Tuberculosis, 44 and diabetes mellitus. 45 Optimal control modeling analysis were very effective in epidemical studies implementing effective control measures for disease annihilation found in References 46-50.…”
Section: Background and Motivationmentioning
confidence: 99%
See 3 more Smart Citations
“…Several fractional studies of deterministic, stochastic and incommensurate models on COVID-19 illness were delved in the literature examining various fear factors, diagnosed, threatened, awareness of pathogen spread, vaccination schemes, vaccine hesitancy, vaccine inefficacy, treatment, isolation, exposure to the virulent environment, effective vaccination with self-precautions, vaccine breakthrough infections, symptomatic and asymptomatic carriers and mutant strains, and so on. [30][31][32][33][34][35][36][37][38][39][40][41][42] COVID-19-related coinfections were studied with other superinfections namely hepatitis-B, 43 Tuberculosis, 44 and diabetes mellitus. 45 Optimal control modeling analysis were very effective in epidemical studies implementing effective control measures for disease annihilation found in References 46-50.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Motivated from the works of References 30,31 which explains the hesitation and threatening of virus, isolation effects, vaccination and environmental exposure, age factors, demographic changes, 32,33 symptomatic and asymptomatic carriers and mutations visualized in References 34,35, fear effects due to isolation and quarantine, vaccination, self‐precautionary measures, and associated coinfections studied in References 36–45. However, we present vaccine breakthrough infections, vaccine efficiency and microbial pathogen coinfections in a novel way on our proposed COVID‐19 coinfection model.…”
Section: Covid‐19 Coinfection Model Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…The traditional SEIR model is equivalent to the Markov chain that includes the four states: S(Susceptible), persons who have no immunity to the virus and are not yet infected, and if they contact with someone who is already infected, they may be infected; E(Exposed), persons who have been infected but have no corresponding symptoms, and they are temporarily not contagious; I(Infected), persons who are already infected and there are corresponding symptoms with them, and they are contagious; R(Removed), persons who have dropped out of the model, which included two parts: those who are successfully cured and return to normal, and those who are dead after treatment failure. At present, many scholars have simulated and analyzed the novel coronavirus epidemic through SEIR model and its derivative models [2][3][4][5][6][7][8][9]. According to Reference 1 [1], the mathematical expression of the modified SEIR model is shown in Equation 1.…”
Section: The Modified Seir Modelmentioning
confidence: 99%